Clocks, Watches and Timepieces: The Ace Bio-Political Tools - Butola, Balbir Singh (Scientific Research Publishing, 2014)
“...it’s my hypothesis that the individual is not a pre-given entity which is seized on by the exercise of power. The individual, with his identity and characteristics, is the product of a relation of power exercised over bodies, multiplicities, movements, desires, forces.” Michel Foucault. All relations are power relations. The sources of power vary from divine (supernatural) to mundane. Every age remains obsessed with its own power relations. Scholars believe that the post-enlightenment age is obsessed with two main sources of power. The Marxists are obsessed with economic (material) power articulated through class domination in the form of relations of production and forces of production. The liberals are obsessed with the existence of power centres articulated through certain institutions, which in turn play a significant role in generating legitimacy to the state. Foucault, while disagreeing with these formulations, believed that the enlightenment movement brought in a major paradigm shift in the then existing power relations. Thereafter, the paradigm “Power is knowledge” was replaced by “Knowledge is power”. Foucault believed that, “Knowledge is not for knowing, knowledge is for cutting”. Cutting means constructing not only the narratives and discourses but also the reality itself. But, unlike the Marxists and the Liberals Foucault did not emphasised on the macro attributes like economic structure and state. For him the micro attributes (capillary, subterrain) of power were more important than the macro. Meaning thereby, the centre or focal point of power are less significant as compared to the “power at its’ extremities, in its ultimate destinations, with those points where it becomes capillary, that is, in its more regional and local forms and institutions”. Clocks, watches and time-pieces are some of these capillary powers that have become the ace tools in the age of bio-politics in controlling the life and its processes.
Keywords: Chronarchy; Ontological Metamorphosis; Unilateralism; Inexatitudes; Sociological ClocTemporal Rationality